Relationship Knowledge Transmission of COVID-19 and Fear of Dental Care During Pandemic in South Sulawesi, Indonesia - Burhanuddin Daeng Pasiga (Association of Support to Oral Health Research (APESB), 2021)
Objective: To determine the relationship of transmission of COVID-19 virus knowledge with dental care during a pandemic. Material and Methods: Online questionnaire using Google forms distributed through social media (WhatsApp groups, Facebook, line groups) using a combination of convenience and snowball sampling. The level of knowledge about coronavirus transmission was measured using a questionnaire consisting of 5 statement items. This questionnaire uses the Guttman scale with 3 response and anxiety categories for dental care as measured using a modified questionnaire from the Dental Fear Survey. This questionnaire consisted of 9 question items using a Likert scale. Results: 285 respondents came from WhatsApp media users (89.9%) with an average age of 29.91 years. Respondents who experienced "dental health problems" during the pandemic were 44.7%. The knowledge of respondents about the transmission of the COVID-19 virus in dental care was 79.9% and the knowledge of the fear of caring during the pandemic period was 31.85% afraid. Statistical analysis showed a significant relationship between knowledge about transmission of the COVID-19 virus and fear of dental care (rs=0.388, p<0.001). Conclusion: The results obtained have a significant relationship between knowledge about transmission and fear for dental care during the COVID-19 pandemic in South Sulawesi Province.